(untitled) (Journal of EAHIL, 2017)
The EAHIL 2014 conference provided the opportunity to present a piece of work carried out by a team of information professionals for RARE-Bestpractices (RBP), an international project to promote exchange of information and knowledge in rare disease. The authors work for Healthcare Improvement Scotland (HIS), a publicly funded organisation which uses evidence, scrutiny and improvement science to facilitate the delivery of safe, effective and patient-centred healthcare. HIS is one of fifteen European partners contributing to RBP with our team providing the core information professional support for the project. Work to develop a rare disease guideline search protocol was presented in order to raise awareness of RARE-Bestpractices, and to demonstrate the engagement of information professionals in multidisciplinary research projects.